Real-World Treatment Patterns and Survival Outcome in Advanced Anaplastic Lymphoma Kinase (ALK) Rearranged Non-Small-Cell Lung Cancer Patients - Britschgi, Christian; Addeo, Alfredo; Rechsteiner, Markus; Delaloye, Raphaël; Früh, Martin; Metro, Giulio; Banini, Marco; Gautschi, Oliver; Rothschild, Sacha I.; Wild, Peter J.; Banna, Giuseppe L.; Curioni-Fontecedro, Alessandra (Frontiers in Oncology, 2020)
Introduction Survival of ALK-rearranged NSCLC patients has dramatically improved by the use of multiple ALK-tyrosine kinase inhibitors (ALK-TKI). However, still little is known about the impact of drug sequencing and clinical features on survival in a real-world setting. Methods Patients with stage IV ALK-rearranged NSCLC treated at six centres in Switzerland and Italy were identified and standard clinical variables collected. OS curves were constructed using the Kaplan-Meier method and compared with the log-rank test. Multivariate Cox proportional hazard analysis was applied to determine the correlations between clinical features and OS. In four patients, biopsies were subjected to NGS. Results 121 patients with stage IV ALK-rearranged NSCLC diagnosed between 2011 and 2016 were included. With a median follow-up time of 39.5 months, the median OS from diagnosis of stage IV disease was 48.0 months. First-line treatment consisted of an ALK-TKI in 24% of patients, with crizotinib in 83% of them. Chemotherapy as first-line treatment did not influence OS (p=0.955). The use of more than one ALK-TKI line positively correlated with OS (p=0.016), as well as the use of alectinib or lorlatinib in any treatment line, as compared to the use of crizotinib ± ceritinib (p=0.022). A never smoking history was an independent prognostic factor for OS (p=0.032). Moreover, treatment with alectinib significantly improved OS. Conclusions Targeted treatment for ALK-positive NSCLC patients lead to prolonged OS. Smoking status was a negative independent prognostic factor in a multi-variate analysis. The use of alectinib or lorlatinib in any treatment line improved overall outcome.